POLITICAL ECONOMY OF REORGANIZATION OF SPACE - Altinok, Emrah; Enlil, Zeynep (YILDIZ TECHNICAL UNIV, 2012)
This paper intends to interpret and explain the spatial reflections of neoliberalism, with an urban political economy perspective. Accordingly, David Harvey's theory of Spatio-Temporal Fixes and Accumulation by Dispossession approach were taken as the primary reference point for this explanation.
Keywords: Urban political economy; reorganization of space; Engineering